Ibn Hazm's views on Islamic ethics with special reference to Kitab al- Akhlaq wa-al-Siyar - Zakariya, Hafiz (Science domain, 2020)
Ibn Hazm is one of the most profound thinkers Muslims ever produced. Despite his pre-eminence, he has been comparatively neglected in the mainstream scholarship. Ibn Hazm is a multi-talented scholar whose influence transcends knowledge boundaries. In fact, he is a renowned traditionist, historian of religion, theologian, philosopher great theoretician of the Zahiri School and so forth. Further, he is claimed to have written four hundred volumes on various disciplines. This article provides a historical analysis of the life and times of Ibn Hazm. It discusses the biography, religio-intellectual milieus of al-Andalus during Ibn Hazm's lifetime, the salient aspects of Ibn Hazm's ideas and his views on Islamic ethics. This study primarily adopts the methods of textual analysis. As ideas do not develop in isolation from the larger contexts, the textual analysis method is aided by the method of historical research.